Odpowiedź :
Odpowiedź:
Funkcja liniowa y = ax + b
a > 0 - funkcja rosnąca
a = 0 - funkcja stała
a < 0 - funkcja malejąca
---------------------------------------------------
A)
y = (m - 3)x + 5
a = m - 3
m - 3 > 0
m > 3 - funkcja rosnąca
m - 3 = 0
m = 3 - funkcja stała
m - 3 < 0
m < 3 - funkcja malejąca
B)
y = (m² - 4)x - 14
a = m² - 4
m² - 4 > 0
(m -2)(m + 2) > 0
m - 2 < 0 ∧ m + 2 < 0 ∨ m - 2 > 0 ∧ m + 2 > 0
m < 2 ∧ m < - 2 ∨ m > 2 ∧ m > - 2
m < - 2 ∨ m > 2
m ∈ (- ∞ , - 2 ) ∨ m ∈ ( 2 , + ∞ ) - funkcja rosnąca
m² - 4 = 0
(m - 2)(m + 2) = 0
m - 2 = 0 ∨ m + 2 = 0
m = 2 ∨ m = - 2 - funkcja stała
m² - 4 < 0
(m - 2)(m + 2) < 0
m - 2 < 0 ∧ m + 2 > 0 ∨ m - 2 > 0 ∧ m + 2 < 0
m < 2 ∧ m > - 2 ∨ m > 2 ∧ m < - 2
m < 2 ∧ m > - 2
m ∈ ( - 2 , 2 ) - funkcja malejąca
Szczegółowe wyjaśnienie:
∧ - znaczy "i"
∨ -znaczy "lub"